Pengembangan lembar kerja peserta didik (LKPD) berbasis inkuiri terbimbing pada materi sistem persamaan linear dua variabel (SPLDV) kelas VIII SMP Muhammadiyah Rambah Hilir - Prabowo; Afri, Lusi Eka; Annajmi (Karoteh Utama, 2023)
This study aims to develop a Validated Guided Inquiry-based Student Worksheet (LKPD) in Mathematics, focusing on systems of linear equations with two variables. The research method employed is Research and Development (R&D), consisting of four stages: Define, Design, Develop, and Disseminate, although in this study, it only reached the development stage. The subjects of this research were eighth-grade students at SMP Muhammadiyah Rambah Hilir during the second semester of the academic year 2022/2023. The validation instrument used in this study was a validation questionnaire. The result of this research is a Guided Inquiry-based LKPD. Based on the validity test conducted by three validators with several revisions and improvements, the average validation score for the Guided Inquiry-based LKPD is 3.55, categorized as